Applied RNA Bioscience (Springer Singapore, 2018)
The focus of this book is to introduce up-to-date information on applications and practical use of RNA for agriculture, biotechnology and medicine. It provides unique ideas, tools, and methods in detail from a variety of scientific and technical disciplines. RNA science has progressed enormously in recent decades, and vast amounts of information on RNA functions and their regulatory mechanisms are becoming available. Such a progress opened the door to an age of practical application of RNA in many fields including agriculture, plant science, medical science, brewing and fermentation technology, and material production. This book inspires its readership and contributes to not only expansion in application of RNA but also to basic research. .